Advances in Cosmic Ray Muon Computed Tomography and Fieldable Spectroscopy - Chatzidakis, Stylianos; Bae, Junghyun (HNPS Advances in Nuclear Physics, 2022)
A recent example of successful technology transition from high energy physics to practical engineering applications is cosmic ray muon tomography. Cosmic ray muon tomography, is a promising non-destructive technique that has been recently utilized to monitor or image the contents of dense or well shielded objects, typically not feasible with conventional radiography techniques, e.g., x-ray or neutron. Cosmic ray muon tomography has been used with various levels of success in spent nuclear fuel monitoring, volcano imaging, and cargo container imaging. Further, knowledge of cosmic ray muon momentum spectrum has the potential to significantly improve and expand the use of a variety of recently developed muon-based radiographic techniques. However, existing muon tomography systems rely only on muon tracking and have no momentum measurement capabilities which reduces the image resolution and requires longer measurement times. A fieldable cosmic ray muon spectrometer with momentum measurement capabilities for use in muon tomography is currently missing. In this paper, we will discuss and explore recent advances in cosmic ray muon computed tomography and spectroscopy and their applications to engineering including a new concept for measuring muon momentum using multiple gaseous Cherenkov radiators. By varying the pressure of multiple gas Cherenkov radiators, a set of muon momentum threshold levels can be selected that are triggered only when the incoming muon momentum exceeds that level. As a result, depending on the incoming muon momentum, none to all Cherenkov radiators can be triggered. By analyzing the signals from each radiator, we can estimate the actual muon momentum.